Welfare and Inequality in Marketizing East Asia - London, Jonathan D. (Studies in the Political Economy of Public Policy,, 2018)
The world-scale expansion of markets and market relations ranks among the most transformative developments of our times. We can refer to this process by way of a generic if inelegant term - marketization. This book explores how processes of marketization have registered across East Asia's diverse social landscape and its implications for patterns of welfare and inequality. While there has been great interest in East Asia's economic rise, treatments of welfare and inequality in the region have been largely relegated to specialist literatures. Proceeding from a synthetic critique of political economy, this book places welfare and inequality at the center of a more encompassing comparative approach to political economy that construes countries as dynamic, globally embedded social orders defined and animated by distinctive social relational and institutional features.